2022
DOI: 10.3390/su14074280
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Industrial Green Transformation in the Process of Urbanization: Regional Difference Analysis in China

Abstract: Population mobility and the expansion of construction land in industrial development promote urbanization, and the sustainable development of cities creates requirements for the green transformation of industry. This paper uses the directional distance function (DDF) and the global Malmquist–Luenberger (GML) index method—including urbanization factors—to calculate the industrial green transformation (IGT) index in China, and to analyze its evolution and spatial distribution characteristics. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…This may be due to the fact that cities in the eastern region have developed infrastructure, technology levels, and highly skilled personnel that can facilitate digitization and innovation levels. Therefore, cities have the highest level of green transformation development and can best alleviate the URG [123]. The "latecomer advantage" in infrastructure and technology in the central region has a slightly weaker dampening effect on the URG than in the eastern region.…”
Section: Discussion On the Heterogeneous Influencementioning
confidence: 99%
“…This may be due to the fact that cities in the eastern region have developed infrastructure, technology levels, and highly skilled personnel that can facilitate digitization and innovation levels. Therefore, cities have the highest level of green transformation development and can best alleviate the URG [123]. The "latecomer advantage" in infrastructure and technology in the central region has a slightly weaker dampening effect on the URG than in the eastern region.…”
Section: Discussion On the Heterogeneous Influencementioning
confidence: 99%
“…There is a mutually reinforcing and interdependent symbiotic relationship between industrialization and urbanization. Industrialization provides the material foundation and economic support for urbanization, while urbanization provides a vast market and labor resources for industrialization (Yue & Zhang, 2022). As urbanization continues to advance, industrialization has undergone further development, giving rise to a new stage of urban industrialization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(3) Studies on the driving forces of IGT. Scholars focused on the impact of environmental regulation [24,25], technological innovation [26,27], energy consumption [28], and urbanization [29] on IGT. Zhai and An found that environmental regulation, as a moderating variable, positively influences the green transformation of manufacturing by acting on technological progress and government behavior [30].…”
Section: Literature Reviewmentioning
confidence: 99%